The Tort Caused by the Transmission of Coronavirus Infection (A comparative study) - Al Abboudi, Nawras (Journal of Legal Sciences, 2022)
The English judge while dealing with the contractual breach، takes into account an aim that the legal solution he makes consistent with justice. Such concept allows the judge to order for the specific enforcement of the debtor’s contractual obligation if the compensation was not a sufficient remedy to redress the damage resulting from that breach. However، the conditions imposed by the rules of justice and the impediments that make the technical scope of this remedy very limited in the positive aspect. And modest in his negative one '' injunction''. Despite of its complementary function among the remedies for contractual breach، specific enforcement in English law may affect legal consequences because of its unique nature، some of which may make the debtor liable in accordance with the penal law.